Photocurrent spectroscopy of dye-sensitized carbon nanotubes - Alam, Asiful; Zakharko, Yuriy; Graf, Arko; Zaumseil, Jana (Nanoscale, 2017)
Monochiral (7,5) single walled carbon nanotubes (SWCNTs) are integrated into a field effect transistor device in which the built-in electric field at the nanotube/metal contact allows for exciton separation under illumination. Variable wavelength spectroscopy and 2D surface mapping of devices consisting of 10-20 nanotubes are performed in the visible region and a strong correlation between the nanotube's second optical transition (S22) and the photocurrent is found. After integration, the SWCNTs are non-covalently modified with three different fluorescent dye molecules with off-resonant absorption maxima at 532 nm, 565 nm, and 610 nm. The dyes extend the absorption properties of the nanotube and contribute to the photocurrent. This approach holds promise for the development of photo-detectors and for applications in photovoltaics and biosensing.